A sensitive and simple electrochemical technique for detecting ascorbic acid content in pharmaceutical and biological compounds - Sayed Zia Mohammadi; Farideh Mousazadeh (Journal of Electrochemical Science and Engineering, 2022)
In the current study, a glassy carbon electrode (GCE) modified with graphene-CoS2 nanocomposite was investigated for electrochemical sensing of ascorbic acid. The electrochemical performance of the modified electrode was examined using differential pulse voltammetry (DPV), linear sweep voltammetry (LSV) and chronoamperometry (CHA) techniques. The electrochemical behavior of ascorbic acid at the graphene-CoS2/GCE displayed a higher oxidation current and lower oxidation potential than bare GCE. Under the optimal experimental conditions, the sensor presented a good linear response between the current and the ascorbic acid concentration range of 0.15–245.0 μM, with a low detection limit of 0.05 μM. Finally, the graphene-CoS2 nanocomposite-modified GCE was applied for the determination of ascorbic acid in real samples and displayed excellent recoveries.